Satellite InSAR data : reservoir monitoring from space - Ferretti, Alessandro (Education tour series., 2014)
This book provides a step-by-step introduction to satellite radar sensors, SAR imagery, SAR interferometry and advanced InSAR techniques. Rather than a tutorial for remote sensing specialists, the book starts from very basic concepts and explains in plain language the most important ideas related to SAR data processing and why geoscientists and engineers should take a vested interest in this new information source. --